Luther and the girls: religious denomination and the female education gap in 19th century Prussia - Sascha O. Becker; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2008)
Martin Luther urged each town to have a girls' school so that girls would learn to read the Gospel, evoking a surge of building girls' schools in protestant areas. Using county- and town-level data from the first Prussian census of 1816, we show that a larger share of Protestants decreased the gender gap in basic education. This result holds when using only the exogenous variation in Protestantism due to a county's or town's distance to Wittenberg, the birthplace of the Reformation. Similar results are found for the gender gap in literacy among the adult population in 1871.
Keywords: I21; J16; N33; Z12; 330; Gender gap; education; protestantism; Frauenbildung; Protestantismus; Geschlechterdiskriminierung; Bildungschancen; Preußen